Illustrations to “Dialogues of the Dead”: a Problem of the Validation of the Title of the Russian Emperor in the 18th Century - Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2015)
Being a form of politically-charged advocacy journalism, in the 18th century a genre of “Dialogues of the Dead” was to contribute to the discussion of a newly-gained title of a Russian ruler — a title of the Emperor. It is treated both in Russian works, which suggest growing ambitions of the Russian state, and in European ones, indicative of the response to them from abroad. A series of “Dialogues” by a German writer D. Fassman demonstrates gradual recognition of Russia’s new status in the international arena during the second quarter of the 18th century, as reflected in the validation of the title of Russian Emperor. Engraved illustrations on frontispieces embody the perception of Russia and Russian monarch and in some cases add new tints to the text. The evolution of the genre is evident in “Conversation of portraits and medallions”, written by Catherine II on the Chesme Palace (not earlier than the late 1770s) which featured a gallery of painted portraits of European monarchs — Catherine II’s contemporaries and bas-relief portraits of her predecessors on the Russian throne — Russian princes, tsars and Emperors. A modified subject-matter as well as the literary style makes it more compelling than traditional “Dialogues of the Dead”. Pieces of art are no longer accompanying material (illustrations), but a source of inspiration for creating a text. “Dialogues of the dead” chimed brilliantly with the way of artistic thinking typical for 18th century, with its specific figurative historicism, reflected in bringing together historical characters from different epochs.
Keywords: Dialogues of the Dead; a title of the Russian Emperor; German advocacy journalism of the second quarter of the 18th century; Rossica; Russia in perception of foreigners; dynastic portrait galleries; a word and an image; book illustration